Identifying processes underlying the multimedia effect in testing: An eye-movement analysis. (February 2017) - Lindner, Marlit Annalena; Eitel, Alexander; Strobel, Benjamin; Köller, Olaf
Abstract: Test items become easier when a representational picture visualizes the text item stem; this is referred to as the multimedia effect in testing. To uncover the processes underlying this effect and to understand how pictures affect students' item-solving behavior, we recorded the eye movements of sixty-two schoolchildren solving multiple-choice (MC) science items either with or without a representational picture. Results show that the time students spent fixating the picture was compensated for by less time spent reading the corresponding text. In text-picture items, students also spent less time fixating incorrect answer options; a behavior that was associated with better test scores in general. Detailed gaze likelihood analyses revealed that the picture received particular attention right after item onset and in the later phase of item solving. Hence, comparable to learning, pictures in tests seemingly boost students' performance because they may serve as mental scaffolds, supporting comprehension and decision making. Highlights: Representational pictures in test items fostered students' test performance. Pictures reduced reading time of the text but enhanced overall item-stem processing. Pictures can serve as scaffolds in the information-acquisition phase of item solving. Pictures can help mental model updating in the decision-making phase of item solving. Our findings suggest that multimedia learning theories can be transferred to testing.